Wind Energy Potential: A Case Study Of Mersing, Malaysia - Nortazi, Sanusi; Azami, Zaharim; Sohif, Mat (Asian Research Publishing Network (ARPN), 2016)
The findings regarding the wind velocity and its contribution to the power of wind energy are discussed in this paper. It involves a statistical analysis of its wind regime, the probability distribution of wind speed and power analysis. A rigorous selection of the probability distribution leads to an unambiguous power analysis. The main distribution selected is Weibull and Gama probability distribution. The wind power equation is derived through transformation method and the outcome of wind power analysis demonstrates the feasibility for the efficient extraction of wind energy in Malaysia. This paper suggests the potential of Mersing area for generating wind power.